2021
DOI: 10.1021/acs.biomac.1c00140
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of Lignin–Cellulase Interactions in Aqueous Solutions

Abstract: Efficient enzymatic hydrolysis of cellulose in lignocellulose to glucose is one of the most critical steps for the production of biofuels. The nonproductive adsorption of lignin to expensive cellulase highly impedes the development of biorefinery. Understanding the lignin–cellulase interaction mechanism serves as a vital basis for reducing such nonproductive adsorption in their practical applications. Yet, limited report is available on the direct characterization of the lignin–cellulase interactions. Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 69 publications
(114 reference statements)
0
13
0
Order By: Relevance
“…In this pH range, the net surface charge of PSA lignin was also reported to be negative ( Chen et al, 2017 ; Luo et al, 2020a ). Therefore, we infer that electrostatic attraction ( Wang et al, 2013 ) and cation-π interaction ( Zheng et al, 2021 ) would be not the main factors governing the efficient blocking of PNVCL towards PSA lignin. Because of the negative surface charge, the PNVCL coating formed on the surface of PSA lignin may further inhibit the adsorption of cellulase via electrostatic repulsion.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In this pH range, the net surface charge of PSA lignin was also reported to be negative ( Chen et al, 2017 ; Luo et al, 2020a ). Therefore, we infer that electrostatic attraction ( Wang et al, 2013 ) and cation-π interaction ( Zheng et al, 2021 ) would be not the main factors governing the efficient blocking of PNVCL towards PSA lignin. Because of the negative surface charge, the PNVCL coating formed on the surface of PSA lignin may further inhibit the adsorption of cellulase via electrostatic repulsion.…”
Section: Resultsmentioning
confidence: 93%
“…This indicates that PNVCL can not only be adsorbed on the surface of the hydrophobic PSA lignin film, but also form a hydrophilic coating after shielding the PSA lignin. Previous studies have found that hydrophilic surfaces could be easily hydrated, which would facilitate the inhibition of protein fouling induced by the hydrophobic interaction ( Cai et al, 2017a ; Cai et al, 2017b ; Wang et al, 2020 ; Zheng et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These peaks were showed in the spectra of DCF/AL and DCF/AL@GO-0.03. No new peak was detected for DCF modified with AL or GO indicating that: (i) the cross-linking took place without the formation of the chemical bonds mentioned before; (ii) due to the large number of chemical bonds already present in the cottonseed protein, it was not possible to detect the formation of any additional new bonds due to the overlap of several peaks in the fingerprint regions; and (iii) the combination between lignin and cottonseed protein was the cation-π interaction [ 14 ]. However, the effects of AL or GO on cottonseed-based adhesives could be readily confirmed using other characterization techniques, including thermal stability, sol-gel analysis, and wet adhesion test.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was reported that lignin is readily combined with protein to form a hydrophobic aggregation. For example, enzymatic hydrolysis of lignocellulosic biomass was accelerated in the solution containing soybean protein and protease as a result of lignin can form a strong intermolecular force with proteins [ 13 , 14 ]. Besides, when lignin was added to the soybean-based adhesive, it displayed performances on improved thermal stability or reduced the pores and cracks on the surface, and thus enhanced water resistance [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%